Large landslides and deep-seated gravitational slope deformations in the Czech Flysch Carpathians: New LiDAR-based inventory - Pánek, Tomáš; Břežný, Michal; Kapustová, Veronika; Lenart, Jan; Chalupa, Vladimír (Geomorphology (Amsterdam, Netherlands), 2019)
Moderate-relief landscapes, such as the Czech Flysch Outer Western Carpathians (COWC), in comparison with alpine regions are rarely subject to extensive landslide inventory mapping. An understanding of landslides in such a landscape is needed, because densely populated hilly landscapes in temperate zones are usually of major socio-economic importance. In this study, we performed the first LiDAR-based landslide mapping for the entire COWC area (~7539 km2), one of the most landslide-prone regions in Europe. By calculating various landscape and landslide metrics, we infer the distribution, frequency-area relationships, kinematics and controls of mass movements with special attention on large landslides (≥0.1 km2) and deep-seated gravitational slope deformations (DSGSDs). We mapped a total of 13,611 landslides, of which 1357 failures are large landslides and DSGSDs. Whereas the lower and more subdued areas in the southern part of COWC are hotspots in terms of the total number of landslides, the higher and more topographically pronounced areas in the northeast are affected predominantly by large landslides and DSGSDs. However, landslides with ≥0.1 km2 are widespread throughout the whole territory of COWC. A discrepancy also exists in the spatial distribution of different types of landslides. Rock slides and DSGSDs are dominant in the north-east, while flow-type landslides are dominant in the southern lower topographic relief with claystone-dominated flysch. We conclude that 1) distinct geological units (nappes) produce landslide populations with different frequency-area distributions; 2) stratigraphic composition alongside the tectonic style of flysch formations control the type of landslides; 3) DSGSDs affect mainly slopes formed by rigid rocks sitting atop soft formations; and 4) geological conditions, rather than topography, control distribution of large landslides and DSGSDs in COWC. [Display omitted] •New LiDAR-based inventory of landslides in the Czech Outer Western Carpathians (COWC)•More than 13,600 landslides are mapped, of which 1357 slope failures are large landslides (≥0.1 km2) and DSGSDs.•Large landslides and DSGSDs are widespread throughout the whole territory of COWC.•Geology rather than topography controls the distribution of large landslides and DSGSDs in the COWC.